Liking Low-Status? Contextual and Individual Differences in Attributional Biases of Low-Status Outgroup Members - Besta, Tomasz; Akbas, Gülçin; Renström, Emma A.; Kosakowska-Berezecka, Natasza; Vazquez, Alexandra (Journal of Social and Political Psychology, 2019)
Previous studies on biased intergroup perceptions of outgroups’ irrationality mostly treated the target groups as opponents and rivals. In three studies, we extended this line of research and tested the hypothesis that individuals who challenge the existing social hierarchy exhibit more positive biases toward low-status outgroup members. We also hypothesized that when irrational thinking is framed as an important human trait, this bias is reduced among low social dominance orientation (SDO) individuals. In three studies (N = 169, N = 450, and N = 161), conducted in countries that vary in power distance levels (Poland, Spain, Sweden and Turkey), we examined under which conditions low-status outgroups are perceived as more rational than ingroup members. The results show that in a condition without irrationality framed as a human trait, psychology students (Study 1 and Study 2) and nonstudents low in group-based dominance orientation (Study 3) perceive outgroup members as less irrational than ingroup members. However, when participants were reminded that irrationality is a human trait, the perceived differences between in- and outgroup members were reduced. This effect was observed in all four countries (Study 1 and Study 2) and held when variables related to the tendency to behave in a socially desirable way were controlled for (Study 3).